IMPLEMENTATION OF THE CALCULATION OF SOME PROBLEMS OF LIMIT THEOREMS IN THE STATISTICA 10 PACKAGE - Kasimov M; Khodzhaniyazov Azamat Genjebaevich; Khalknazarov Askar Makhsetbaevich; Nurmakhanov Kayrat Erpayizovich (Utilitas Mathematica, 2025)
The main objective of this paper is to solve the central limit theorem problems presented in the STATISTICA 10 package with the possibility of computer implementation.